2014
DOI: 10.6065/apem.2014.19.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disorders and the neurologic manifestations

Abstract: The nervous system and the endocrine system are closely interrelated and both involved intimately in maintaining homeostasis. Endocrine dysfunctions may lead to various neurologic manifestations such as headache, myopathy, and acute encephalopathy including coma. It is important to recognize the neurologic signs and symptoms caused by the endocrine disorders while managing endocrine disorders. This article provides an overview of the neurologic manifestations found in various endocrine disorders that affect pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…For example, hypocalcemia can arise at any age and affects the majority (>60%) of adult patients [Cheung et al, 2014b; McDonald-McGinn et al, 2015]. While often asymptomatic, hypocalcemia can be associated with neuropsychiatric symptoms, including irritability, fatigue, tremor, muscle cramps, stiffness, and seizures [Bassett et al, 2011; Kao et al, 2004; Weinzimer 2001; Yu 2014]. Notably, some anticonvulsants, e.g., carbamazepine, phenytoin, may diminish vitamin D levels [Teagarden et al, 2014], potentially increasing the risk of hypocalcemia [Cheung et al, 2014b] and its associated complications.…”
Section: General Principles Of Management For Neuropsychiatric Disordmentioning
confidence: 99%
“…For example, hypocalcemia can arise at any age and affects the majority (>60%) of adult patients [Cheung et al, 2014b; McDonald-McGinn et al, 2015]. While often asymptomatic, hypocalcemia can be associated with neuropsychiatric symptoms, including irritability, fatigue, tremor, muscle cramps, stiffness, and seizures [Bassett et al, 2011; Kao et al, 2004; Weinzimer 2001; Yu 2014]. Notably, some anticonvulsants, e.g., carbamazepine, phenytoin, may diminish vitamin D levels [Teagarden et al, 2014], potentially increasing the risk of hypocalcemia [Cheung et al, 2014b] and its associated complications.…”
Section: General Principles Of Management For Neuropsychiatric Disordmentioning
confidence: 99%
“…It has been reported that SARS-CoV-2 can cross the blood-brain barrier (BBB) and infect the ACE2 expressing neurons and glial cells, thereby leading to neuroinflammation and neuropathogenesis in the brain regions including the hypothalamus that controls various physiological functions like maintenance of the body temperature and hormonal balance [8,12,17,25,26]. Dysregulation of endocrine functions is an important clinical issue as it is related to different disorders including hypothyroidism, hypogonadism, anxiety, stress, and depression that are clearly evident in COVID-19 cases [27][28][29][30]. While the possible impact of COVID-19 on the abnormal hypothalamic-pituitaryadrenal (HPA) axis has been speculated [31], SARS-CoV-2mediated dysregulation of the hypothalamic-pituitary-gonadal (HPG) axis remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with endocrine disorders may experience neurologic diseases [6]. Among endocrine disorders, thyroid disorders have been known as risk factors for progressive cognitive impairment development, either in the form of hyperthyroidism or hypothyroidism [7].…”
Section: Introductionmentioning
confidence: 99%